Pengaruh lama waktu inkubasi, konsentrasi starter terhadap pH, viskositas dan sifat organoleptik yoghurt susu sapi - Rachmat Adiputra; Mita Ramadiyanti; Triana Ulfah; Dini Islah Maesaroh (University of Insan Cendekia Mandiri, 2022)
This research was conducted to determine the effect of incubation time and starter concentration on pH, viscosity, and organoleptic properties of cow's milk yogurt. This research was conducted from 16 to 23 June 2019 located at FIYO Yoghurt owned by Mr. Engkos Zakaria which is located in Pameungpeuk Village RT 03 RW 12 Pasirhalang Village, Cisarua District, West Bandung Regency. This study used a completely randomized design (CRD) factorial design consisting of two factors and three replications. The first factor is the length of incubation time (W) consisting of three levels, namely w1 = 3 hours incubation time, w2 = 6 hours of incubation time and w3 = 9 hours of incubation time. The second factor is the starter concentration (S) consisting of 3 levels, namely s1 = 2% starter concentration, s2 = 4% starter concentration and s3 = 6% starter concentration. From the research results it can be concluded that there has been an interaction between the length of incubation time and the concentration of the starter on the viscosity of cow's milk yogurt. The best interaction occurred at 9 hours of incubation time and 6% starter concentration. 9 hours incubation time and 6% starter concentration had a good effect on pH and viscosity. While the incubation time of 6 hours and 6% starter concentration produced organleptic properties which were quite liked by the panelists